IMPLEMENTASI KEBERHASILAN PROGRAM CO-OP (Cooperative Academic Education) DIKTI DALAM MENCIPTAKAN HUBUNGAN KEMITRAAN ANTARA DUNIA USAHA-DUNIA INDUSTRI (DUDI) DAN PERGURUAN TINGGI (Studi Pelaksanaan Program Co-op Di STIENU Jepara) - Widiastuti, Anna (STIE YPPI Rembang, 2012)
Form of partnership relations between universities and industry has become a necessity for allparties. Moreover talk about results that must be prepared by a college for graduates. With theestablishment of the relationship expected such an activity that needed each other and mutuallybeneficial. Through the co-op of DIKTI, STIENU Jepara has conducted activities partnershipwith company partner. The purpose of this research is to know implementation successprogram co-op ( cooperative academic education ) DIKTI in creating a partnership betweenDUDI and college (Studies of Co-op Programs at STIENU Jepara). Scope directed in thisresearch is research is descriptive qualitative, with respondents research is a student programparticipants co-op, colleges and UMKM partners program co-op STIENU Jepara, and as ayardstick success gainful partnership were the feedback systems between DUDI and collegesand student participants. The result of this research is the implementation of the program coopDIKTI received by STIENU Jepara very positive impact, good for students direct program, asof an offender lecturers as a mentor, the agency that accommodates as well as for the companyor UMKM partners program. Where via this program could raise soffskill of all the offenderwhether in respect to increase expertise, responsibility and corporateness.Keywords: The Co-op Program, Partnership college and DUDI